Maqashid Syariah: Konsep dan Implementasinya Dalam Hukum Islam Kontemporer - Amaliya, Denti (Maliki Interdisciplinary Journal, 2024)
The concept of Islamic law known as “maqashid sharia” aims to achieve benefit and avoid harm for mankind. This concept centers on the protection of five major aspects of life: religion (hifz ad-din), soul (hifz an-nafs), intellect (hifz al-aql), offspring (hifz an-nasl), and property (hifz al-mal). Maqashid sharia has become an important foundation in contemporary Islamic law to resolve modern issues such as Islamic economics, human rights, and the environment. This method sees Islamic law as a set of textual rules and tools to achieve goals that evolve with the times. The purpose of applying maqashid sharia in modern Islamic law is to ensure that Islamic values remain relevant in addressing the complex social, political, and economic dynamics of the globalization era, so that Islamic principles can continue to contribute to the well-being of humanity.